The Accountability of Pondok Pesantren’s Financial Management: The Central Role of Kiai Leadership - Abdul Rohman; Tri Jatmiko Wahyu Prabowo; Ahmad Nurkhin (Economics Education Department Universitas Negeri Semarang, 2025)
This study seeks to examine the factors influencing the financial management accountability of Pondok Pesantren, with a particular emphasis on the pivotal role of Kiai leadership. By using structural equation modeling (SEM), this paper focuses on several key variables, namely Kiai leadership, human resource (HR) competency, perception of accounting standards, and information technology (IT) usage. The research was carried out at a Salafiyah Pondok Pesantren, involving students, asatidz councils, and administrators as respondents. Data was collected from 140 respondents using purposive sampling. Data was collected through a questionnaire and analyzed using SEM to examine both direct relationships and indirect (mediated) effects among the study variables. The findings of the study suggest that the leadership of the Kiai and the competency of human resources play a vital role in shaping Pesantren's financial accountability. In contrast, the adoption of information technology and the perception of accounting standards do not significantly impact. Furthermore, Kiai leadership strongly influences HR competency, IT usage, and perceptions of accounting guidelines. The study also reveals that HR competency significantly mediates Kiai leadership and financial accountability. These results emphasize the strategic importance of strengthening HR capabilities and reaffirm Kiai leadership's central role in enhancing financial management practices' accountability in Pesantren.